An original inverse kinematics algorithm for kayaking - Fohanno, V.; Begon, M.; Colloud, F.; Lacouture, P. (ISBS - Conference Proceedings Archive (Konstanz), 2009)
For some sports, e.g. kayaking and rowing, ecological conditions represent a challenge for collecting three-dimensional kinematics. The lower-limbs are partially hidden by the boat and motion analysis systems used in laboratory are not suitable for outdoor and on-water measurements. An inverse kinematics (IK) approach has been proposed where a few tasks would be measured by inertial sensors or inclinometers (Begon & Sardain, 2007). However, due to the lack of actual kinematics, the authors could not assess its reliability. The purpose of this study is to assess the accuracy of this IK algorithm by comparison with a standard algorithm of global optimization.